A piano in the house eaudiobook - Hamner, Earl, Jr (Twilight Zone Radio Dramas., 2013)
Insensitive drama critic Fitzgerald Fortune buys his young wife a player piano as a birthday present. To his surprise, he discovers it has magical properties: its music reveals people's hidden fears, loves, thoughts and secrets.